(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Dry eye disease (DED) is considered as one of the most prevalent ophthalmological illnesses, caused by a number of systemic and ocular etiologies, including meibomian gland dysfunction (MGD). Medical students are among the high-risk group for developing DED during the COVID-19 pandemic, primarily because visual display terminals (VDTs) are being used more frequently for online courses. During the Covid 19 pandemic curfew there is anincrease in usage of digital devices for mandatory e-learning leads to increased exposure of screen time among medical students. Objective:The aim of this study to estimate the prevalence of DED among undergraduate medical students. Methodology:A prospective, Cross Sectional Study was conducted among 250 UG students. After getting informed consent all participants were assessed using the Ocular Surface Disease Index (OSDI) questionnaire, Routine ophthalmological examination along with schrimer test and tear film break-up time (TBUT) as a screening tool for detecting DED.The Data thus collected is entered in Microsoft excel sheet & analyzed using SPSS software version 22.0.Descriptive statistics were applied to summarize the demographic data. Chi-square tests were used for comparisons between categorical variables. Results:Among the 250 students 104 (41.6%) were males and 146 (58.4%) were females with the Mean age was 21.17 ± 1.2. The prevalence of dry eye disease among study participants was 56.8% (142). On OSDI classification of severity grading 89(41.6%) students had mild DED, 48(13.2%) of students had moderate DED and 5 (21.0%) of students had severe DED. Conclusion:The study highlighted the drastic increase in use of digital devices after the initiation of the COVID-19 lockdown and there is an increase in prevalence of DED among medical students. Awareness about prevention of digital eye strain should be enforced to bring these adverse effects to a minimum level.